التحول الحفزي للميتانول على الزيوليت السوري وعلى الزيوليت NaX المحمّل بالحديد والزنك (Latakia University Journal -Basic Sciences Series, 2018)
درسنا تحول الميتانول على عينة من الخامات السورية الحاملة للزيوليت، وأجرينا مقارنة مع تحول الميتانول على الزيوليت NaX المحمل بالحديد والزنك. تبين أن هناك اختلافاً في البنية المسامية، وحيث تحوي عينة الزيوليت السوري على مسامات من النوع ميزو بشكل أساسي، بينما العينات الأخرى تحوي على مسامية دقيقة بشكل أكبر. تكون الفعالية الحفزية لعينة الزيوليت السوري أكبر وبشكل واضح من العينات الأخرى، وتصل إلى 88.6 % عند الدرجة 400oC وتتمتع بانتقائية عالية بالنسبة لإنتاج قطفة البنزن وتصل إلى 78.4 % . بينما تكون فعالية العينة NaX أخفض من ذلك بكثير وعند جميع درجات الحرارة.تزداد الفعالية الحفزية بوجود الحديد والزنك على NaX . يكون التحول الأساسي للميتانول على عينة الزيوليت السوري باتجاه الحصول على قطفة البنزن C5+ ، بينما يكون التحول الأساسي على العينات الأخرى هو إنتاج الهيدروكربونات C1-C4. تختلف نسبة المركبات C1-C4 باختلاف درجة الحرارة. We had studied the conversion of methanol on Syrian ore containing zeolite, and compared it with NaX zeolite loading Fe and Zn. There is a difference in the chemical composition and in the texture of the samples. Syrian zeolite contains mesoporous mainly, while the others are microporous. The catalytic activity of the Syrian zeolite is more than NaX, and reaches to 88.6% at 400oC, and this sample has a high selectivity to produce the benzene fraction, and the selectivity was 78.4%. The activity of the NaX was minimal at all temperatures. We noted that the activity of the NaX increased when the Fe and Zn are present. The main product of the conversion of methanol on the Syrian zeolite was benzene fraction, and low percent of C1-C4 hydrocarbons, while the product on the other samples was C1-C4 only. The content of C1-C4 was different depending on the temperature for all samples.